Reflections on the Context of Public Law and Private Law on the Example of the Decision to Permit a Road Investment - Gawrecki, Bartłomiej Mikołaj (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The article aims to show the next points of contact between public law and private law by presenting the civil and administrative legal effects of the decision on the permit for the implementation of a road investment (including its amendment and repeal), referred to in the Act of April 10, 2003, on special rules for the preparation of and implementation of investments in the field of public roads. The reason for the author to analyze the topic was the fact that the author has noticed the increasingly stronger interpenetration of the areas of public law and private law and problems encountered in legal practice. The article is a synthesis of the civil and administrative legal consequences – sometimes unintentional – of issuing and changing the decision on the permit for the implementation of a road investment, which have their source in the unilateral, imperative action of a competent public administration body. It is also another voice in the discussion on the advisability of the classic division into the two oldest branches of law.